Drug design : principles and applications - Grover, Abhinav (Springer, 2017)
This book offers an in-depth discussion of the latest strategies in the field of drug design and their applications in various disorders, in order to encourage readers to undertake their own projects. It also includes the contemporary application of drug-designing methodologies to inspire others to further expand the utility of this field in other diseases. It is intended for advanced undergraduate and graduate students, postdocs, researchers, lecturers and professors in bioinformatics, computational biology, medicine, pharmaceutics and other related fields.
Keywords: Drugs -- Design.; elektronické knihy; electronic books